Narasi Kebijakan Pemindahan Ibu Kota Negara Indonesia: Analisis Hastags di Twitter - Tri, Tri Rahayu Ramadhani; Hermansyah; Mursak; Muhammad Takdir; Baharuddin (Sawala : Jurnal Administrasi Negara, 2024)
Efforts to move the state capital from DKI Jakarta to East Kalimantan are precisely between North Penajam Paser Regency and Kutai Kartanegara Regency. Twitter is present as one of the popular social media and the most effective source channel of communication and information. Problems related to the relocation of the capital of Indonesia (IKN) arise due to various narratives and opinions from the public on social media, especially on Twitter through various hashtags. Some people have responded and rejected this policy. Therefore, this research emerged because of a narrative on social media Twitter in the form of hashtags related to the transfer policy of the national capital (IKN). The purpose of this study is to find out what are the narratives on Twitter social media in the form of hashtags supporting and rejecting related to the transfer policy of the Indonesian capital and the percentage of people who accept or reject these narratives. This study uses a qualitative method with a case study approach. There are descriptions of various perspectives and narratives that appear on Twitter social media in the form of hashtags related to the transmission policy of the Indonesian capital city, reflecting the complexity of the issue in society. From the Communication Content on Twitter Based on data analysis using hashtags, it shows that the Indonesian people, both the government and the public are very enthusiastic in campaigning for the IKN to inform the issue of the relocation of the National Capital City (IKN) in Indonesia.